2022
DOI: 10.51620/0869-2084-2022-67-6-355-361
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream infection in hospital therapeutic patients

Abstract: Bloodstream infection (BI) is the cause of high mortality. Hospital bloodstream infection (HBI) complicates hemodialysis, pneumonia, oncohematological diseases. Positive hemoculture obtaining depends on the volume of blood inoculation, the number of blood samples, the incubation time. To test the principles of microbiological culturomics in the diagnosis BI of hospital patients with a therapeutic profile. 848 hospital cardiac patients with suspected BI were included. 10 ml of blood were taken intravenously wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
0
1
1
Order By: Relevance
“…Contrary to prior research, our study suggests an increased risk of Gram-negative rod bloodstream infection from bacterial translocation in females compared to males in rural settings [ 21 , 22 ]. Previous studies indicated that females are more susceptible to urinary tract infections due to anatomical differences, a common precursor to bloodstream infections [ 21 , 22 ]. The heightened risk of bacterial translocation in females observed in our study might be explained by variations in healthcare utilization patterns [ 23 , 24 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to prior research, our study suggests an increased risk of Gram-negative rod bloodstream infection from bacterial translocation in females compared to males in rural settings [ 21 , 22 ]. Previous studies indicated that females are more susceptible to urinary tract infections due to anatomical differences, a common precursor to bloodstream infections [ 21 , 22 ]. The heightened risk of bacterial translocation in females observed in our study might be explained by variations in healthcare utilization patterns [ 23 , 24 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Некоторые из них, в частности, С.striatum, вызывают инфекции, связанные с оказанием медицинской помощи (ИСМП) [10,11]. У пациентов с гематологическими заболеваниями С. striatumи C. jeikeium являются основными видами рода Corynebacterium, вызывающими инфекции кровотока [12][13][14]. Эти виды коринебактерий выделяют, в том числе, при бактериемии из крови у пациентов с COVID-19 [13].…”
Section: Rostov-on-don Plague Control Research Institute; 344002 Rost...unclassified